A kinematic and kinetic analysis of the influence of chains on the technical execution of the snatch - Coker, C. (Research Quarterly for Exercise and Sport, 2005)
Ziel der Studie war die Untersuchung des Einflusses von Ketten auf die technische Ausführung des Reißens im Gewichtheben.